The Effect of Debt Default, Audit Tenure and Liquidity on Going Concern Audit Opinion Acceptance - Novia Dian Anggraini; Netty Herawty; Rico Wijaya (Harmoni Economics: International Journal of Economics and Accounting, 2024)
This study aims to find out how Debt Default, Audit Tenure and Liquidity can affect the acceptance of the Going Concern Audit Opinion (Empirical Study on Manufacturing Companies in Various Industrial Sectors listed on the IDX for the 2019-2022 period). The sample in this study is Manufacturing Companies in the Various Industrial Sectors using the Purposive Sampling technique so that 26 companies with 4 years of observation (104 observation data) were obtained that met the criteria. The data used is in the form of secondary data obtained from the company's annual report through the Indonesia Stock Exchange (IDX) website and the official website of the related company. Researchers use a quantitative approach to describe research problems through trend descriptions or being able to explain the relationship between variables. The analysis technique used in this study is data analysis using descriptive statistical analysis and logistic regression analysis with the help of SPSS 30 software. The method of data collection is by means of documentation and literature study. The results of the study concluded that Debt Default significantly affected the acceptance of going concern audit opinions, while Tenure and Liquidity Audit did not significantly affect the acceptance of going concern audit opinions.